In Vitro and In Vivo Inhibitory Activities of Selected Traditional Medicinal Plants against Toxin-Induced Cyto- and Entero- Toxicities in Cholera - Rajitha Charla; Priyanka P. Patil; Arati A. Bhatkande; Nisha R. Khode; Venkanna Balaganur; Harsha V. Hegde; Darasaguppe R. Harish; Subarna Roy (Toxins, 2022)
Careya arborea, Punica granatum, Psidium guajava, Holarrhena antidysenterica, Aegle marmelos, and Piper longum are commonly used traditional medicines against diarrhoeal diseases in India. This study investigated the inhibitory activity of these plants against cytotoxicity and enterotoxicity induced by toxins secreted by Vibrio cholerae. Cholera toxin (CT) and non-membrane damaging cytotoxin (NMDCY) in cell free culture filtrate (CFCF) of V. cholerae were quantified using GM1 ELISA and cell-based assays, respectively. Hydro-alcoholic extracts of these plants and lyophilized juice of P. granatum were tested against CT-induced elevation of cAMP levels in CHO cell line, binding of CT to ganglioside GM1 receptor and NMDCY-induced cytotoxicity. Significant reduction of cAMP levels in CFCF treated CHO cell line was observed for all extracts except P. longum. C. arborea, P. granatum, H. antidysenterica and A. marmelos showed >50% binding inhibition of CT to GM1 receptor. C. arborea, P. granatum, and P. guajava effectively decreased cytotoxicity and morphological alterations caused by NMDCY in CHO cell line. Further, the efficacy of these three plants against CFCF-induced enterotoxicity was seen in adult mice ligated-ileal loop model as evidenced by decrease in volume of fluid accumulation, cAMP levels in ligated-ileal tissues, and histopathological changes in intestinal mucosa. Therefore, these plants can be further validated for their clinical use against cholera.